2018
DOI: 10.1038/s41396-018-0196-8
|View full text |Cite
|
Sign up to set email alerts
|

Microbial island biogeography: isolation shapes the life history characteristics but not diversity of root-symbiotic fungal communities

Abstract: Island biogeography theory is one of the most influential paradigms in ecology. That island characteristics, including remoteness, can profoundly modulate biological diversity has been borne out by studies of animals and plants. By contrast, the processes influencing microbial diversity in island systems remain largely undetermined. We sequenced arbuscular mycorrhizal (AM) fungal DNA from plant roots collected on 13 islands worldwide and compared AM fungal diversity on islands with existing data from mainland … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 69 publications
2
68
0
1
Order By: Relevance
“…Yet these macroecological approaches will be less effective in providing relevant outputs at national scales if they are based on data extrapolated from other countries; they would be strongly improved if local data were made available 25,112 . Without more comprehensive studies seeking answers to large-scale soil ecological questions -often involving dealing with multiple scales (temporal and spatial) and a number of thematic and taxonomic depths 75 -it is difficult to deepen soil macroecological knowledge 113 . This is particularly relevant in testing biodiversity and ecosystem function relationships at the global scale, or trying to address specific societal issues (e.g., the attribution of climate and land-use change as drivers of soil ecological change or general biodiversity trends) 17 .…”
Section: Challenges To Move Beyond Blind Spotsmentioning
confidence: 99%
“…Yet these macroecological approaches will be less effective in providing relevant outputs at national scales if they are based on data extrapolated from other countries; they would be strongly improved if local data were made available 25,112 . Without more comprehensive studies seeking answers to large-scale soil ecological questions -often involving dealing with multiple scales (temporal and spatial) and a number of thematic and taxonomic depths 75 -it is difficult to deepen soil macroecological knowledge 113 . This is particularly relevant in testing biodiversity and ecosystem function relationships at the global scale, or trying to address specific societal issues (e.g., the attribution of climate and land-use change as drivers of soil ecological change or general biodiversity trends) 17 .…”
Section: Challenges To Move Beyond Blind Spotsmentioning
confidence: 99%
“…Cork & Kenagy, ; Claridge et al ., ). However, dispersal by terrestrial mammals and underground invertebrates is limited to short and medium distances and cannot explain the colonisation of discontinuous territories (McIlveen & Cole, ; Mangan et al ., ; Davison et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…One of the confirmed co‐dispersers of seeds and AM fungal diaspores, the European robin, is partially migratory with migrations across the entire Western Palearctic region (Adriaensen & Dhondt, ; Pérez‐Tris et al ., ; Ambrosini et al ., ). Recently, it was found that AM fungal communities on islands are as diverse as mainland communities, suggesting that the island biogeography of AM fungi is characterised by an efficient dispersal that outweighs the potential effects of speciation and extinction (Davison et al ., ). Thus, birds might be important vectors for the long‐distance dispersal of AM fungi with the additional advantage of transporting seeds of their symbiotic partners into particularly suitable germination sites (Wenny, ; Traveset et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has traditionally been assumed that, compared with other fungi, arbuscular mycorrhizal (AM) fungi disperse relatively ineffectively due to their large soil‐borne spores (Smith & Read, ). Yet, recent studies have shown that many AM fungi exhibit cosmopolitan distributions, suggesting that long‐distance dispersal mechanisms operate within the group (Davison et al ., , ). Although there is evidence for multiple potential dispersal vectors for AM fungi – both abiotic (water and air/wind; Harner et al ., ; Egan et al ., ) and biotic (animals, including humans; Mangan & Adler, ; Rosendahl et al ., ; Lekberg et al ., ; Nielsen et al ., ) – there has been no direct evidence of long‐distance dispersal until now.…”
mentioning
confidence: 99%